Tafsīr Šaiḫ al-Islām Ibn-Taimīya al-Ǧāmiʿ li-kalām al-Imām Ibn-Taimīya fi 't-tafsīr - Ibn-Taimīya, Aḥmad Ibn-ʿAbd-al-Ḥalīm 1263-1328 (Dār Ibn-al-Ǧauzī lin-Našr wa-'t-Tauzīʿ, 2011)
Koran; commentaries; early works to 1800